Progress of single-cell sequencing technology in immunotherapy for tuberculosis - Fan, Xinxin; Chen, Muxing; Wu, Di; Lin, Youfei; Chen, Xiaohong (Frontiers in Cellular and Infection Microbiology, 2025)
According to the 2024 World Health Organization (WHO)Global Tuberculosis (TB)Report, tuberculosis remains the leading cause of death from a single infectious agent, with 10.8 million new cases and 1.25 million deaths in 2023. Early and standardized treatment upon definitive diagnosis holds significant importance for the prevention and prognosis of pulmonary tuberculosis patients. However, the number of drug-resistant tuberculosis(DR-TB) cases is increasing, while the interventions for tuberculosis are becoming increasingly limited. There is an urgent need to develop new rapid diagnostic methods and effective treatment drugs. Recent advances in tuberculosis immunotherapy have shown promising results. Novel therapeutic vaccines like M72/AS01E demonstrate 54% efficacy in preventing pulmonary TB, while host-directed therapies including nano-based drug delivery systems offer enhanced treatment outcomes. The immune system plays a vital role in the development and regulation of tuberculosis. Single-cell sequencing(SCS) technology enables comprehensive analysis of immune cells at the single-cell level, revealing the functions, states, distributions, and communication behaviors among immune cell subpopulations. These insights contribute to understanding the pathogenesis and discovering new diagnostic markers and therapeutic targets in tuberculosis. This review provides a critical overview of the immunological mechanisms underlying tuberculosis, immunotherapy for tuberculosis, and single-cell sequencing technology, with specific focus on key findings from recent studies and their clinical implications. It primarily focuses on discussing the research progress of single-cell sequencing technology in the context of tuberculosis immunotherapy and identifies current challenges and future research priorities.